Experimental inhibition of a key cellular antioxidant affects vocal communication. (6th February 2017) - Messina, Simone; Eens, Marcel; Casasole, Giulia; AbdElgawad, Hamada; Asard, Han; Pinxten, Rianne; Costantini, David
Summary: There is substantial interest of evolutionary ecologists in the proximate mechanisms that modulate vocal communication. In recent times, there has been growing interest in the role of oxidative stress as a mediator of avian song expression. Here, we tested whether the experimental inhibition of the synthesis of a key cellular antioxidant (glutathione) reduces song rate metrics of male European starlings ( Sturnus vulgaris ). We measured the effect of our treatment on total song rate and on its two components, undirected and nest‐box‐oriented song, outside the breeding season. Treated males that did not own a nest‐box (subordinate males likely to be of lower quality) suffered increased oxidative stress relative to untreated males, while treated males that owned a nest‐box (dominant males likely to be of higher quality) did not. Treated non‐owners also reduced their undirected song rate, whereas treated nest‐box owners did not suffer any reduction in song rate. Our results revealed that inhibition of a key cellular antioxidant results in decreased vocal communication in a social vertebrate, and that this effect is dependent on its social status (nest‐box owner vs. non‐owner). This work provides support for the hypothesis that acoustic signals may honestly convey information about the individual oxidative status and capacity to regulate the oxidative balance. Our findings raise the possibility of hitherto unexplored impacts of oxidative stress on fitness traits in social species. A lay summary is available for this article. Abstract : Lay Summary